WAYS TO IDENTIFY THE COMPLEXITY OF LOGARITHMIC EQUATIONS - Saera Barlikbaeva Jetkerbaevna (International Journal of Innovations in Engineering Research and Technology, 2021)
The purpose of this article is to reveal the content of General methods for solving logarithmic equations studied in high school of the 11th grade.